Bullying Prevention Strategy at State Senior High School 5 Surakarta: The Role of Peer Educators, Parent Involvement, and Cooperation with External Parties - Nurul Istiqomah; Rochman Hadi Mustofa (Universitas PGRI Yogyakarta, 2026)
Bullying among students is one of the serious problems that negatively impacts students' emotional health, social relationships, and academic achievement, and its impact is not only felt by the victim physically and emotionally but also affects the learning atmosphere. This study aims to analyze the implementation of anti-bullying policies in State Senior High School 5 Surakarta, focusing on the role of peer educators, parental involvement, and cooperation with external parties. The method used in this study is qualitative with a case study approach and is located at State Senior High School 5 Surakarta. Data was collected through in-depth interviews and observations. The results of this study show that State Senior High School 5 Surakarta has implemented programs in bullying prevention, including through: (1) the role of peer educators in bullying prevention; (2) parental involvement; and (3) cooperation with external parties. The findings of this study demonstrate that peer educators play a crucial role in preventing and overcoming bullying behavior in the school environment. Furthermore, parental involvement and cooperation with DP3AP2KB significantly strengthen efforts to stop it. Keywords: bullying, peer educator, anti-bullying policy